Optical charge state control of spin defects in 4H-SiC. Issue 1 (December 2017) - Wolfowicz, Gary; Anderson, Christopher; Yeats, Andrew; Whiteley, Samuel; Niklas, Jens; Poluektov, Oleg; Heremans, F. Joseph; Awschalom, David
Abstract Defects in silicon carbide (SiC) have emerged as a favorable platform for optically active spin-based quantum technologies. Spin qubits exist in specific charge states of these defects, where the ability to control these states can provide enhanced spin-dependent readout and long-term charge stability. We investigate this charge state control for two major spin qubits in 4H-SiC, the divacancy and silicon vacancy, obtaining bidirectional optical charge conversion between the bright and dark states of these defects. We measure increased photoluminescence from divacancy ensembles by up to three orders of magnitude using near-ultraviolet excitation, depending on the substrate, and without degrading the electron spin coherence time. This charge conversion remains stable for hours at cryogenic temperatures, allowing spatial and persistent patterning of the charge state populations. We develop a comprehensive model of the defects and optical processes involved, offering a strong basis to improve material design and to develop quantum applications in SiC. Defects in silicon carbide represent a viable candidate for realization of spin qubits. Here, the authors show stable bidirectional charge state conversion for the silicon vacancy and divacancy, improving the photoluminescence intensity by up to three orders of magnitude with no effect on spin coherence.